Natural Features Technique for Non-Contact Three Dimensional Craniofacial Anthropometry Using Stereophotogrammetry - Majid, Zulkepli; Chong, A; Setan, Halim; Ahmad, Anuar; Rajion, Zainul (2006)
This paper describes the use of stereophotogrammetry approach to measure and hence identify accurately three-dimensional (3D) coordinates of important landmarks on a craniofacial surface. A â€œnovelâ€? technique dubbed as â€œnatural featuresâ€? technique was employed to accurately compute the 3D coordinates of selected craniofacial landmarks. The natural features technique involves the use of 3D coordinates of the natural features (such as acne, scar, corners of eyes, edge of mouth, point of chin, etc.) that appear on the craniofacial surface as an absolute stereophotogrammetric mapping control points. The 3D coordinates of the natural features were gained using digital photogrammetric bundle adjustment method. Validation of the proposed technique has firstly been carried out using mannequin and finally, it was applied on the real-life human faces. The result shows that the craniofacial landmark measurement accuracy of 0.8mm with one standard deviation can be successfully achieved by the proposed technique.